The effect of laser-activated Acidulated Phosphate Fluoride on enamel submitted to erosive solution only: an in vitro prelimnary evaluation - (:unkn) unknown (ARIESDUE SRL, 2011)
Aim The purpose of this in vitro study was to evaluate the potential effect of laser therapy on the prevention of erosive demineralisation either alone or combined with acidulated phosphate fluoride gel on human enamel. It was hypothesized that such a treatment would decrease enamel solubility Study Design Efficacy of 2940nm Er:YAG laser with preset parameters - alone or combined with APF (Acidulated Phosphate Fluoride) gel - was tested on freshly extracted human permanent molars. Methods Ten sound human third molars were sectioned into 5 surfaces (2 x 3 mm) with hard tissue microtome and were randomly allocated into different treatment groups as follows. The Vicker's hardness of each surface was obtained at the baseline. Group 1, negative control group: no treatment. Group 2, positive control group: only 1.23% APF gel (Denti-Care gel, Medicom) 1 minute application. Group 3: irradiated with surface modification mode (2940 nm, 1.2j/cm(2), 10Hz, 300 mu m) Er:YAG laser Group 4: Er:YAG laser application following 1.23% APF gel. Group 5: 1.23% APF gel following Er:YAG laser application. The demineralisation process was obtained by immersion of specimens in a soft drink for 10 minutes and then the Vickers hardness was revaluated. Statistics For statistical analyses within groups the Kruskal Wallis test was used, while for comparing groups the paired sample t test (significancy p<0.05) was used. Results The difference in microhardness values of each group obtained following the treatments was not statistically significant (p>0.05). Beside, no statistical difference was found in Vickers value related to the application of fluoride prior or after laser therapy. Conclusion Er:YAG laser irradiation alone or combined with APF decreased the enamel solubility but combined treatment did not show any significant additional effect.
Keywords: Acidulated Phosphate Fluoride; Laser; Microhardness; ER-YAG LASER; DENTAL EROSION; ACID RESISTANCE; CARIES; IRRADIATION; PREVENTION; INHIBITION; TEETH; CO2